A review of current issues of marine current turbine blade fault detection. (15th December 2020) - Xie, Tao; Wang, Tianzhen; He, Qianqian; Diallo, Demba; Claramunt, Christophe
Abstract: Marine current turbines (MCTs) has progressively attracted wider interest from the industry and many research initiatives due to its potential as a novel world energy resource. However, several technological issues amongst others fault detection of MCT blades still require further progress for their successful implementation. Indeed, power generation is likely to progressively degrade due to blade faults and then causes disruptive disturbance when the marine current generator is connected to the grid. Fault detection of MCT blades still presents several challenges due to the complexity of the underwater environment. It appears that attachment like plankton or biofouling may have a considerable influence on the turbine blade as these may be triggering different imbalance faults. This survey reviews different blade fault types under the condition of wave and turbulence. We also review current blade fault detection methods, including multi-domain approaches. It appears from our study that built-in sensor-based fault detection methods, which use phase currents and voltages across the generator windings, provide several advantages for MCT blade fault detection. It also proposes several trends. Highlights: An overview of marine current turbine (MCT) blade fault detection is given. We analyze the pros & cons of MCT blade fault detection methods. Four research directions for future research work are also suggested.